Wood property improvement of siberian pine by combination of boric acid impregnation and insitu polymerization of ?-caprolactone - Ermeydan, Mahmut Ali; Dizman Tomak, Eylem; Kartal, Zeynep Nur (My University, 2019)
Wood is an excellent engineering material with its light weight and high mechanical properties. However, it is susceptible to biodegradation due to its hygroscopic nature and chemical composition that limits both its indoor and outdoor usage. Boron compounds which are known as eco-friendly wood preservatives have limited utility at outdoor conditions since they are easily leached out from wood by water. The aim of this study is to prevent boron leaching by creating a polymer network that encapsulates boron compound inside the wood cell walls, thus decay resistance, dimensional stability and water repellence are improved. In the study, Siberian pine samples were impregnated with 1% boric acid in DMF(N,N-Dimethylformamide) and further ?-caprolactone monomer (1% SnOct2 as initiator) mixture for further in-situ polymerization were carried out in the oven at 150°C for 3 hours. Prior to decay testing, leaching test was conducted in order to evaluate any loss in effectiveness in decay resistance against to C. puteana and C. versicolor attack due to possibility of boron leaching from wood. The results showed that leached samples had lower weight loss than unleached samples after C. puteana attack, however, the weight loss by C. versicolor attack increased in leached samples. Decay resistance of treated samples was found to be 7-99% in comparison with references. Boric acid and polymer combination increased dimensional stability (25% ASE), and water repellence (15%) of wood compared to references without deformation. This method showed that curing may be an alternative for wood modification with in-situ polycaprolactone polymerization in order to use hazardous solvent media for polymerization.
Keywords: Bilgisayar Bilimleri, Donanım ve Mimari; Bilgisayar Bilimleri, Bilgi Sistemleri; Bilgisayar Bilimleri, Yazılım Mühendisliği; Mühendislik, Kimya; Mühendislik, Elektrik ve Elektronik; Mühendislik, Jeoloji; Mühendislik, Makine